2007
DOI: 10.1097/01.tp.0000295989.63674.53
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Renal Dysfunction in Lung Transplant Recipients

Abstract: Several factors predispose to renal dysfunction (RD), a common complication of solid organ transplants. We evaluated the impact of clinical and laboratory parameters on the decline of renal function in lung and heart-lung transplant recipients. We enrolled 45 patients who survived more than 6 months after transplantation, had normal renal function and urinalysis before the surgery. The prognostic value of variables for the occurrence of RD was calculated by univariate analysis. Thirty patients developed RD, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
4
8
0
1
Order By: Relevance
“…However, DSC is the most frequently used endpoint in research on this topic, facilitating comparison between studies. 11,19 Our results are strengthened by the parallel findings with the gold standard 125 I-Iothalamate GFR measurements. 13 Another strength of this study is its large, well-characterized cohort of LTRs, including all patients transplanted at our center since the start of the program, without any loss to follow-up.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, DSC is the most frequently used endpoint in research on this topic, facilitating comparison between studies. 11,19 Our results are strengthened by the parallel findings with the gold standard 125 I-Iothalamate GFR measurements. 13 Another strength of this study is its large, well-characterized cohort of LTRs, including all patients transplanted at our center since the start of the program, without any loss to follow-up.…”
Section: Discussionsupporting
confidence: 69%
“…This is an acknowledged end-point in clinical studies on chronic renal function impairment, including LTx. 4,[17][18][19] Accordingly, DSC was defined as the first SCr value twice the baseline value, confirmed by a similar second value at least 4 weeks after the initial doubling. Baseline SCr was the mean of available measurements in the month prior to transplantation.…”
Section: End-pointsmentioning
confidence: 99%
“…The present study was not designed to measure the specific impact of aprotinin use in lung transplant patients, but its identification as an independent predictor of ARF serves to heighten the concerns about its safety in cohorts other than cardiac revascularization surgery. In accordance with other risk factors for ARF published in the literature, the present study also considered patient gender, the diagnosis of pre-operative arterial hypertension, the diagnosis of idiopathic pulmonary hypertension, the prolonged length of stay in the intensive care unit, the use of antibiotics, the use of radiographic contrast dye, the use of the cardiopulmonary bypass, and the use of calcineurin inhibitors in the immediate post-operative period, among others, as potential risk factors [21,22]. Of these factors, some were included in the multivariate model, while others were denied.…”
Section: Discussionmentioning
confidence: 77%
“…Calcineurin inhibitor therapy has long been associated with a decline in kidney function and incident CKD in solid-organ transplantation [25][26][27]. We found that CyA use was an independent risk factor for persistent AKI, with its mechanism being potentially related not only to systemic exposure but also dependent on individual variability and local kidney factors [28].…”
Section: Comparison To Previous Studies and Interpretation Of Resultsmentioning
confidence: 93%